Pengukuran Produktivitas Tenaga Kerja pada Proyek Swakelola XYZ - Pratiwi, Katarina Dian; Triana, Masca Indra; Firmansyah, Mohamad (CV. Information Technology Training Center - Indonesia (ITTC), 2025)
Worker productivity is one of the factors that determines the success of a project. The XYZ construction project is a self-managed project. Productivity can be measured using the Labor Utilization Rate (LUR) method. Labor Utilization Rate (LUR) is an indicator that shows the portion of work time actually spent by workers on productive tasks during the observation period. Researchers measured LUR using work sampling, a random observation method that records worker activities at various times to illustrate the utilization of work hours in the field. During the observation, observers recorded the time, location, and type of activity using a simple form. This study collected data directly on the finishing work of the XYZ Project. Observations were conducted on five workers over six days, resulting in a total of 30 samples. Worker activities were recorded at specific intervals from 8:00 a.m. to 5:00 p.m. WIB. In addition, researchers also collected data on respondent characteristics through a questionnaire covering age, education, work experience, and length of service on the project. The combination of work sampling and questionnaires provides a more comprehensive picture of labor productivity. Measurement results showed that the ceramic tile installation job had the highest LUR value at 55.67%, while the wall demolition on the second day had the lowest value at 51.73%. An LUR value in the 50–60% range indicates moderate or fairly effective productivity. This indicates that worker performance is quite good, but there is still unproductive time that needs to be minimized. Indicator evaluation showed that time management is the most influential factor on productivity, with the highest score on indicator X4.6 at 3.73. Conversely, mastery of technical skills was the weakest factor, with a score of 3.20 on indicator X3.3. Thus, despite good time discipline, productivity is still hampered by limited technical competency and a suboptimal compensation system.